1983
DOI: 10.1152/ajpgi.1983.245.5.g690
|View full text |Cite
|
Sign up to set email alerts
|

beta-Adrenergic control of exocrine secretion by perfused rat pancreas in vitro

Abstract: To investigate the role of beta-adrenergic receptors in the genesis of pancreatic juice, we studied the effect of the agonist isoproterenol (25 or 2.5 mumol X 1(-1] on the isolated perfused rat pancreas and compared it with the effect of secretin (approximately 3 nmol X 1(-1). Isoproterenol stimulated flow of a HCO3-rich juice; the response was qualitatively similar to that evoked by secretin, but the flow rate was only about 70% of the maximum in vitro secretin response. We also studied the effects of the aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
13
1

Year Published

1984
1984
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 0 publications
6
13
1
Order By: Relevance
“…Pearson & Singh (1983) have demonstrated an increase in amylase secretion following field stimulation of rat pancreatic fragments, a response abolished by propranolol. This work confirms that of Lingard & Young (1983) who also demonstrated that amylase secretion could be evoked in the isolated perfused rat pancreas by the fl-adrenergic agonist isoprenaline.…”
Section: Discussionsupporting
confidence: 91%
“…Pearson & Singh (1983) have demonstrated an increase in amylase secretion following field stimulation of rat pancreatic fragments, a response abolished by propranolol. This work confirms that of Lingard & Young (1983) who also demonstrated that amylase secretion could be evoked in the isolated perfused rat pancreas by the fl-adrenergic agonist isoprenaline.…”
Section: Discussionsupporting
confidence: 91%
“…The present results clearly demonstrate that adrenergic stimulation does not affect pancreatic amylase secretion in contrast to previous studies (Lingard and Young, 1983;Pearson and Singh, 1983;Pearson et al, 1984). In view of the suggestion that adrenergic stimulation indirectly influence secretion via changes in pancreatic blood MacLachlin, 1917), we used dispersed pancreatic acini to assess direct involvement cf catecholamines in pancreatic amylase secretion.…”
Section: Discussioncontrasting
confidence: 67%
“…Many studies have also been published on pancreatic amylase release in response to sympathomimetic drugs (Demol and Sarles, 1980;Furuta et al, 1978;Hubel, 1970;Pederson and Schultz, 1974;Raptis et al, 1973;Lingard and Young, 1983). Recently, Pearson et al, reported that stimulation of adrenergic receptor induced pancreatic amylase secretion in isolated segments of rat pancreas (Pearson and Singh, 1983;Pearson et al, 1984).…”
mentioning
confidence: 99%
“…Propranolol blocked this inhibition and had no effect on the response to cholecystokinin. These observations suggest that (1) terbutaline inhibits pancreatic secretion by a beta-adrenergic mechanism and (2) the primary effect of terbutaline on canine exocrine pancreas is inhibition of water and bicarbonate secretion.Other investigators demonstrated beta-adrenergic in fluences on in vitro rat pancreatic secretion [1,2]. Addi tionally, we have shown that terbutaline, a beta-adrener gic agonist, inhibits in vivo canine pancreatic secretion evoked by cholecystokinin [3], secretin [4] and a liquid meal [5].…”
mentioning
confidence: 70%